1998
DOI: 10.1016/s0925-4773(98)00174-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct but overlapping expression patterns of two vertebrate slit homologs implies functional roles in CNS development and organogenesis

Abstract: The Drosophila slit gene (sli) encodes a secreted leucine-rich repeat-containing protein (slit) expressed by the midline glial cells and required for normal neural development. A putative human sli homolog, SLIT1, has previously been identified by EST database scanning. We have isolated a second human sli homolog, SLIT2, and its murine homolog Slit2. Both SLIT1 and SLIT2 proteins show approximately 40% amino acid identity to slit and 60% identity to each other. In mice, both genes are expressed during CNS deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
2
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 37 publications
5
121
2
2
Order By: Relevance
“…In vertebrates, Slits have been shown to repel several types of extending axons as well as migrating neurons Hu, 1999;Li et al, 1999;Nguyen Ba-Charvet et al, 1999;Niclou et al, 2000;Wu et al, 1999;Zhu et al, 1999). The complementary expression of Slits and Robos during vertebrate development Holmes et al, 1998; and the binding of Slit and Robo in cellular assays Li et al, 1999;Chen et al, 2000) suggest that the Robo-Slit receptor-ligand relationship is conserved in vertebrates, but the functions of vertebrate Robos are largely unproven, especially in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vertebrates, Slits have been shown to repel several types of extending axons as well as migrating neurons Hu, 1999;Li et al, 1999;Nguyen Ba-Charvet et al, 1999;Niclou et al, 2000;Wu et al, 1999;Zhu et al, 1999). The complementary expression of Slits and Robos during vertebrate development Holmes et al, 1998; and the binding of Slit and Robo in cellular assays Li et al, 1999;Chen et al, 2000) suggest that the Robo-Slit receptor-ligand relationship is conserved in vertebrates, but the functions of vertebrate Robos are largely unproven, especially in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…While the expression patterns of slit1, 2, and 3 have been examined in detail (e.g., Itoh et al, 1998;Holmes et al, 1998;Li et al, 1999;, the expression studies of vertebrate robos are much less complete. The expression patterns of mammalian robo1 and 2 have been studied in the developing spinal cord Wang et al, 1999;, eye (Erskine et al, 2000;Niclou et al, 2000;Ringstedt et al, 2000), kidney (Piper et al, 2000), olfactory bulb, and hippocampus (Nguyen Ba-Charvet et al, 1999).…”
Section: What Are the Roles Of Zebrafish Robos During Embryogenesis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Three vertebrate Slit proteins have been identified as the ligands of Robo receptors and shown to act as repellent molecules (Holmes et al, 1998;Itoh et al, 1998;Brose et al, 1999;Li et al, 1999;Yuan et al, 1999b). The vertebrate Slit proteins have been shown to bind Robo1 and Robo2 proteins in cell binding and immunoprecipitation assays (Brose et al, 1999;Li et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified three members of the mouse Slit family (Holmes et al, 1998;Itoh et al, 1998;Nakayama et al, 1998). Among these, Slit1 and Slit2 are expressed in the septum at E12.5 Tuyen et al, 1999) (Fig.…”
Section: Effects Of Removal Of the Septum And Inhibition Of Endogenoumentioning
confidence: 90%